2017
DOI: 10.3847/2041-8213/aa8db8
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive Evolution of Nonlinear Fast Magnetoacoustic Wave Trains

Abstract: Quasi-periodic rapidly propagating wave trains are frequently observed in extreme ultraviolet observations of the solar corona, or are inferred by the quasi-periodic modulation of radio emission. The dispersive nature of fast magnetohydrodynamic waves in coronal structures provides a robust mechanism to explain the detected quasiperiodic patterns. We perform 2D numerical simulations of impulsively generated wave trains in coronal plasma slabs and investigate how the behavior of the trapped and leaky components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
2
27
0
1
Order By: Relevance
“…This dependence on the driver duration is extremely important in attempts to unlock the seismological potential of these waves. Varying other parameters such as the spatial scale of the driver, and the transverse density profile of the waveguide can have similar effects on the final wave train signature (e.g., Nakariakov et al 2005;Pascoe et al 2013Pascoe et al , 2017Yu et al 2017). Therefore an effort to clearly distinguish these factors in both theoretical and observational studies should be made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dependence on the driver duration is extremely important in attempts to unlock the seismological potential of these waves. Varying other parameters such as the spatial scale of the driver, and the transverse density profile of the waveguide can have similar effects on the final wave train signature (e.g., Nakariakov et al 2005;Pascoe et al 2013Pascoe et al , 2017Yu et al 2017). Therefore an effort to clearly distinguish these factors in both theoretical and observational studies should be made.…”
Section: Discussionmentioning
confidence: 99%
“…The numerical setup is similar to previous studies which have used the 2D slab geometry (e.g., Nakariakov et al 2004;Pascoe et al 2017). The magnetic field is straight and uniform in the z-direction, with strength B 0 .…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We need to stress that specific shapes of the transverse density profile of coronal MHD waveguides, for example, a coronal loop, polar plume, jet, streamer, etc., are not known, but are subject to intensive investigation (see, e.g., Aschwanden & Nightingale 2005;Brooks et al 2013;Arregui et al 2015;Pascoe et al 2017a;Goddard et al 2017Goddard et al , 2018Pascoe et al 2018, for coronal loops). In particular, Pascoe et al (2017b) demonstrated that the accumulation of nonlinear effects in the dynamics of the fast wave trains trapped in coronal plasma slabs is highly inhibited by strong waveguide dispersion, so that even for the relative perturbation amplitudes of several tens of percent the nonlinear steepening of the wave does not occur. The latter result clearly justifies the applicability of the linear MHD theory to modelling fast wave trains in coronal plasma structures.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetohydrodynamic (MHD) waves carry the vital information of the source region, they propagate across structured waveguides, therefore, the analysis of MHD waves could be used to infer the key parameters of both the source and waveguide on the sun, which are not usually measurable in practice. Various types of them have been detected and studied during the last decades, such as coronal extreme-ultraviolet (EUV) waves (e.g., Thompson et al 1998Thompson et al , 1999Liu et al 2010;Warmuth 2010;Warmuth & Mann 2011;Yuan & Nakariakov 2012;Yang et al 2013;Liu & Ofman 2014;Muhr et al 2014;Warmuth 2015;Goddard et al 2016;Kumar et al 2017;Pascoe et al 2017;Shen et al 2018b;Cheng et al 2018;Shen et al 2019;Goddard et al 2019;Pascoe et al 2019), chromospheric Moreton waves (Moreton 1960;Krause et al 2018;Chen & Wu 2011), fast mode (Ofman & Thompson 2002;Liu et al 2011Liu et al , 2012Yuan et al 2013;Zhang et al 2015;Ofman & Liu 2018) and slow mode (e.g., Nakariakov & Zimovets 2011;Yuan et al 2015b) magnetosonic waves. There are various types of waves that can lead to coronal loop and filament oscillations (Nakariakov & Ofman 2001;Nakariakov & Verwichte 2005;Chen et al 2008;Liu et al 2012;Shen et al 2014a,b;Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 99%